Curriculum guidelines, standards and skills in spanish language. from untamed industrial objectivity to student’s harmless subjectivity - Arias Bedoya, Franklin Yessid (Universidad Pedagógica y Tecnológica de Colombia, 2015)
Competency Based Education is a curricular approach that, in addition to the controversy it arises, establishes practices and specific thoughts in schools: its origin from behavioral theories and their connection to the economic field disclose formation objectives that highlight the need of thinking about teaching practices and institutional curricula. These goals linked to projects such as work-oriented education and the propaedeutic cycles reveal the implicit intentions in the education system, where students’ specific characteristics yield to national economic imperatives. This reflection paper seeks to explore and define the ‘conceptual gap’ between an education based on the ideals of trade logic, and one directed to the aesthetic and socio-political formation of the subject, on the basis of legal documents as the Curricular Guidelines, Skill Standards for Spanish Language, Law 39 of 1903, General Law of Education and texts by various educational theorists such as Paulo Freire and Gimeno Sacristan.